2006
DOI: 10.1063/1.2335819
|View full text |Cite
|
Sign up to set email alerts
|

Solitary electrostatic waves are possible in unmagnetized symmetric pair plasmas

Abstract: A possibility of stationary solitary electrostatic waves with large amplitude in symmetric unmagnetized symmetric pair plasmas (e−e+ plasma, C60−C60+ plasma or e−h+ plasma) is proven. The main idea of the work is a thermodynamic unequilibrium of plasma species which may be created in low-density ideal pair plasmas. Ranges of parameters (Mach number M and a nonequilibrium degree τ=T+∕T−) which lead to the possibility of solitary waves are found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…In a recent preprint Dubinov et al 37 reached broadly similar conclusions about the existence range in the parameter space of and M, but only ␥ e = ␥ p = 1 values were studied. Their treatment is based on a Sagdeev approach and on the inversion of the Bernoulli relations ͑15͒ in the limit ␥ e = ␥ p = 1, in terms of the Lambert W function, 38 so that the pseudopotential is expressed in terms of .…”
Section: ͑28͒mentioning
confidence: 68%
See 1 more Smart Citation
“…In a recent preprint Dubinov et al 37 reached broadly similar conclusions about the existence range in the parameter space of and M, but only ␥ e = ␥ p = 1 values were studied. Their treatment is based on a Sagdeev approach and on the inversion of the Bernoulli relations ͑15͒ in the limit ␥ e = ␥ p = 1, in terms of the Lambert W function, 38 so that the pseudopotential is expressed in terms of .…”
Section: ͑28͒mentioning
confidence: 68%
“…39 The range 0 ഛ T p / T e ഛ 1 of the existence domains in Fig. 3 by Dubinov et al 37 corresponds to our Fig. 6, since, as explained, I have chosen to restrict the discussion to that temperature range for reasons of simplicity.…”
Section: ͑28͒mentioning
confidence: 96%
“…On the other hand, the existence of such waves in pair-plasmas assuming a thermodynamic unequilibrium, i.e., when the temperatures of the species are different, has been investigated and confirmed in Ref. 22. In this work, we shall investigate the propagation of ES solitary waves in a collisionless plasma consisting of isothermal electron ͑or negative fullerene ions C 60 − ͒, positrons ͑or positive fullerene ions C 60 + ͒, and stationary heavy positive ions ͑or dust particulates͒.…”
Section: Introductionmentioning
confidence: 94%
“…During this decade, an extensive theoretical research work on linear and nonlinear electrostatic waves in PI plasma has also been carried out. The large amplitude nonlinear electrostatic structures in PI plasmas are studied by Dubinov et al 11 The authors reported that solitary waves formed only when a small difference of temperature exist between the two pair ion species. The solitary structures in symmetric plasmas with gas dynamic approach have also been investigated.…”
Section: Introductionmentioning
confidence: 99%